The influence of vigorous training on the structure and cardiorespiratory fitness in adolescent athletes. (25th November 2020) - Szabo, L; Sydo, N; Kiss, O; Csulak, E; Dohy, Z; Czimbalmos, C; Juhasz, V; Horvath, V; Suhai, F.I; Merkely, B; Vago, H
Abstract: Introduction: The functional and morphological adaptation of the cardiovascular system to vigorous exercise in adolescents is less understood compared to adult athletes. Therefore, the differential diagnosis of normal cardiovascular adaptation from the possible pathological alterations is challenging. Cardiovascular magnetic resonance is an important method for assessing ventricular function and morphology. Maximal oxygen uptake (VO2 max) has been established as a reliable measure of the maximal ability to produce metabolic power aerobically. Aims: The aim of this study was to examine left (LV) and right (RV) ventricular morphologic and functional remodeling in elite adolescent athletes using cardiac magnetic resonance imaging (CMR) and cardiopulmonary exercise test (CPET). Methods: Between 2017 and 2019 116 asymptomatic adolescent (14–20 years) athletes (>6 training hour/week) underwent CMR and CPET as part of a detailed sports cardiology screening. Cine movie images were performed for the quantification of the LV and RV volumes, masses and ejection fraction, and advanced post processing included feature-tracking strain analysis. CPET was performed on a dedicated athlete protocol. Results: All athletes participated in sports with a high dynamic component. Male athletes (n=74, 16±1 years) demonstrated higher LV and RV end –diastolic volume index (EDVi), stroke volume index (SVi) and mass index (Mi) compared with female athletes (p<0.001). We found significant difference regarding the global circumferential strain (GCS) and mechanical dispersion (MD) of male and female athletes (GCS −34±4 vs. −31±5%; MD 4±2 vs. 7±4% p<0.05). VO2 showed positive correlation with the LV and RV volumetric parameters (EDVi, SVi) and Mi (p<0.001) and the absolute value of GCS (p<0.05), and negative correlation with the MD (p<0.001). In 36 athletes the VO2 max exceeded the age-adjusted expected VO2 max by 130%, which was categorized as excellent. Besides gender, age, and body surface area CMR based LVEDVi and LVMi were independent predictors of VO2 max. Conclusion: The functional and morphological adaptation of the adolescent cardiovascular system shows noteworthy differences between male and female athletes. VO2 max correlates with several CMR based values including LV and RV volumetric parameters, masses and strain parameters such as GCS and MD. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Project no. NVKP_16-1-2016-0017 has been implemented with the support provided from the National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. ÚNKP-19-3-I New National Excellence Program of the Ministry for Innovation and Technology.